2017
DOI: 10.1186/s40349-017-0094-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of applied energy in renal sympathetic denervation with magnetic resonance guided focused ultrasound in a porcine model

Abstract: BackgroundPast catheter-based and focused ultrasound renal denervation studies have indicated that procedure efficacy is related to the number of ablations performed or the amount of energy used for the ablation. This study extends those prior results and investigates energy level effects on the efficacy of MR guided focused ultrasound renal denervation performed in a porcine model.MethodsTwenty-four normotensive pigs underwent unilateral denervation at three intensity levels. The applied intensity level was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
2
0
2
Order By: Relevance
“…Insufficiently focused ultrasound delivery can result in inadequate temperature elevation at the target region, which can lead to failure of complete sympathetic nerve disruption. Previous studies ( 18 , 21 , 22 ) highlighted the role of insufficient ablation on the variability of BP response observed following RDN. Furthermore, Sakura et al ( 23 ) reported sympathetic nerve regeneration at 180 days after the RDN procedure with radiofrequency energy, which may be partially explained by insufficient energy delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Insufficiently focused ultrasound delivery can result in inadequate temperature elevation at the target region, which can lead to failure of complete sympathetic nerve disruption. Previous studies ( 18 , 21 , 22 ) highlighted the role of insufficient ablation on the variability of BP response observed following RDN. Furthermore, Sakura et al ( 23 ) reported sympathetic nerve regeneration at 180 days after the RDN procedure with radiofrequency energy, which may be partially explained by insufficient energy delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Swine or canines were used, because their renal systems are similar to those of humans. Several experimental studies [60][61][62][63][64] have shown that extracorporeal focused ultrasound ablation of the renal artery and nerve is safe and effective.…”
Section: Extracorporeal Focused Ultrasoundmentioning
confidence: 99%
“…Persarafan simpatik ginjal memainkan peranan penting dalam patofisiologi hipertensi. 16 Nervus renalis efferen berasal dari otak, melewati medulla spinalis, mencapai ginjal melalui ganglia simpatis, berjalan di tunika adventitia arteri renalis dan menginervasi segmen perifer korteks renalis, kemudian berakhir di arteriol glomerulus. 17 Aktivasi serabut saraf efferen ginjal menyebabkan retensi garam dan cairan dan aktivasi sistem renin-angiotensin-aldosteron, yang pada akhirnya meningkatkan tekanan darah.…”
Section: Renal Denervation (Rdn)unclassified
“…Penelitian pada hewan coba pernah dilakukan pada anjing 11 dan babi. 8,10,16 Dari penelitian tersebut didapatkan penurunan tekanan darah yang signifikan, yakni 15,9 mmHg pada tekanan sistolik dan 13,6 mmHg pada tekanan diastolik. 11 Ditemukan pula penurunan kadar norepinepfrin 8 dan tidak ditemukan adanya kerusakan jaringan sekitar seperti kulit, hepar, lien, ginjal, ureter dan usus halus.…”
Section: Efektivitas Hifu Pada Hipertensi Resistenunclassified